Factors Associated with Exclusive Breastfeeding at Hospital Discharge in Rural Western Australia - Cox, Kylee; Giglia, Roslyn; Zhao, Yun; Binns, Colin (Sage Science Press, 2014)
Background: Breastfeeding is accepted as the best way of feeding infants, and health authorities recommend exclusive breastfeeding to around 6 months of age, but despite the evidence of its benefits, few mothers meet this goal. Infants who are exclusively breastfed in the early postpartum period are more likely to continue breastfeeding at 6 and 12 months, reinforcing the role that Baby-Friendly hospital practices play in supporting exclusive breastfeeding.Objectives: This study aimed to determine the rate of breastfeeding initiation and identify the factors associated with exclusive breastfeeding at discharge from hospital for rural mothers.Methods: The prospective cohort study recruited 489 women from hospitals in regional Western Australia following the birth of their infant. Breastfeeding exclusivity at discharge was assessed based on mothers’ self-reported infant feeding behavior during her hospital stay. The self-administered baseline questionnaire was completed by 427 mothers.Results: Breastfeeding was initiated by 97.7% of the mothers in this cohort, with 82.7% exclusively breastfeeding at hospital discharge. The odds of exclusive breastfeeding at discharge were more than 4 times higher for women whose infants did not require admission to the special care nursery (adjusted odds ratio [aOR] = 4.43; 95% confidence interval [CI], 1.98-9.99). Demand feeding (aOR = 3.33; 95% CI, 1.59-6.95) and 24-hour rooming-in (aOR = 2.31; 95% CI, 1.15-4.62) were also significant positive factors.Conclusion: The findings suggest that hospital practices are strong predictors of exclusive breastfeeding. Greater emphasis on Baby-Friendly hospital practices in the early postpartum period may help the establishment of exclusive breastfeeding, assisting rural mothers to reach established international breastfeeding recommendations.